2016
DOI: 10.1080/1751696x.2016.1244949
|View full text |Cite
|
Sign up to set email alerts
|

Are there alternative adaptive strategies to human pro-sociality? The role of collaborative morality in the emergence of personality variation and autistic traits

Abstract: Selection pressures to better understand others' thoughts and feelings are seen as a primary driving force in human cognitive evolution. Yet might the evolution of social cognition be more complex than we assume, with more than one strategy towards social understanding and developing a positive pro-social reputation? Here we argue that social buffering of vulnerabilities through the emergence of collaborative morality will have opened new niches for adaptive cognitive strategies and widened personality variati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 110 publications
0
23
0
Order By: Relevance
“…It is proposed that technological skills and understanding might have given advantages to hunter gatherer groups, as they do for modern day advances in computer science. Knowledge or memory of important information to do with food resources and their availability or weather changes bring significant advantages to groups, especially at times of hardship or limited resource availability [60].…”
Section: How Long Has Asc Been Around In History/prehistory?mentioning
confidence: 99%
“…It is proposed that technological skills and understanding might have given advantages to hunter gatherer groups, as they do for modern day advances in computer science. Knowledge or memory of important information to do with food resources and their availability or weather changes bring significant advantages to groups, especially at times of hardship or limited resource availability [60].…”
Section: How Long Has Asc Been Around In History/prehistory?mentioning
confidence: 99%
“…From the archeological perspective, however, a recent review mentioned the enhanced perceptual abilities of the individuals with this disorder and argues the possibility that these might contribute the survival of the individuals in a Paleolithic context (Spikins et al, 2016). From a cognitive science perspective, on the other hand, here the author presents experimental evidence indicating the gifted cognitive capability of such individuals and suggests the historical presence of a group of professional individuals who had relied upon the capability to survive, being incorporated into human societies.…”
Section: Introductionmentioning
confidence: 99%
“…Pertinently, the trait of autism (without intellectual impairment) is known to be associated with valuable technical and social skills (Spikins et al, 2016). Hence, autism might not be due to a lack of sociability, but rather to a lack of a rules-based theory of mind, and thus autism might be favorable for innovation Green et al (2010) sequenced the Homo neanderthalensis genome and identified ancestral genes that are "fixed" in present-day humans, together with others that changed over time in Homo sapiens, presumably due to positive selection (Green et al, 2010).…”
Section: Why Has Homo Sapiens Outlasted Other Human Subspecies?mentioning
confidence: 99%
“…Thus, autism might be required for an ability to be both a "generalist" and "specialist". Furthermore, because autism may render people less willing to be followers,Spikins et al (2016) points out that people with autism often attain notable positions in society, particularly in the fields of medicine, engineering, mathematics, physics and information technology. Thus, a key point in human intellectual evolution might be tolerance of a variety of individual characteristics, including autism.…”
mentioning
confidence: 99%